An OER Architecture Framework: Needs and Design - Khanna, Pankaj; Basak, P C (International Review of Research in Open and Distributed Learning, 2013)
This paper describes an open educational resources (OER) architecture framework that would bring significant improvements in a well-structured and systematic way to the educational practices of distance education institutions of India. The OER architecture framework is articulated with six dimensions: pedagogical, technological, managerial, academic, financial, and ethical. These dimensions are structured with the component areas of relevance: IT infrastructure services, management support systems, open content development and maintenance, online teaching-learning, and learner assessment and evaluation of the OER architecture framework. An OER knowledge and information base, including a web portal, is proposed in the form of a series of knowledge repositories. This system would not only streamline the delivery of distance education but also would enhance the quality of distance learning through the development of high quality e-content, instructional processes, course/programme content development, IT infrastructure, and network systems. Thus the proposed OER architecture framework when implemented in the distance education system (DES) of India would improve the quality of distance education and also increase its accessibility in a well-organised and structured way.